Enhanced adsorption capacity of sulfadiazine on tea waste biochar from aqueous solutions by the two-step sintering method without corrosive activator. Issue 1 (February 2021) - He, Xianglei; Li, Jialiang; Meng, Qingmei; Guo, Ziyu; Zhang, Hao; Liu, Yurong
Abstract: The search for a cost-effective and mild activation method of preparing biochar with excellent adsorption capacity is advantageous to broaden its potential industrial application. Accordingly, tea waste was selected as a carbon source, and KHCO3 and CH3 COOK were selected as activators in the two-step sintering process because of their mildness and non-corrosive features. Three types of tea waste biochar was prepared, characterised and utilised for the adsorption of sulfadiazine (SDZ) from aqueous solutions. Benefiting from the activation, the specific surface areas of the tea waste biochar with the highest adsorption capacity described as KHCO3 -TB-1:2 and CH3 COOK-TB-1:2, were 717.636 and 648.415 m 2 /g, respectively, whereas the specific surface area of tea waste biochar that was not activated in the two-step sintering process was named TB was only 4.833 m 2 /g. Moreover, the tea waste biochar that was activated by KHCO3 and CH3 COOK developed a typical micro-/meso-/macro-hierarchical pore structure. Compared to TB without an adsorption capacity, the maximum adsorption capacities of KHCO3 -TB-1:2 and CH3 COOK-TB-1:2 for SDZ were 77.52 and 58.14 mg/g, respectively, at an initial concentration of 50 mg/L and pH = 10.97. The data of the batch-adsorption experiments fitted well with the pseudo-second-order kinetics and Langmuir model, thus suggesting that the adsorption process was dominated by chemical and monolayer adsorptions. The π–π electron donor–acceptor interaction, hydrogen bonding, and electrostatic interaction were the possible adsorption mechanisms. The activation of KHCO3 and CH3 COOK is a very promising method to limit equipment corrosion and prepare biochar for the removal of SDZ from aqueous solutions. Graphical Abstract: ga1 Highlights: Three types of tea waste biochar were prepared by a two-step sintering method. KHCO3 and CH3 COOK were selected as the activator instead of H3 PO4, ZnCl2, and KOH. Two types of biochar have large specific surface and abundant pore structures. Tea waste biochar showed high adsorption of sulfadiazine from aqueous solutions.